2 Receptor Specific Ligand Conjugated Nanocarriers: An Effective Strategy for Targeted Therapy of Tuberculosis - Prabhu, Pratiksha; Fernandes, Trinette; Damani, Mansi; Chaubey, Pramila; Narayanan, Shridhar; Sawarkar, Sujata (Current Drug Delivery, 2022)
Tuberculosis (TB) is an ancient chronic disease caused by the bacillus Mycobacterium tuberculosis, which has affected mankind for more than 4,000 years. Compliance with the standard conventional treatment can assure recovery from tuberculosis, but the emergence of drug-resistant strains poses a great challenge for the effective management of tuberculosis. The process of discovery and development of new therapeutic entities with better specificity and efficacy is unpredictable and time-consuming. Hence, delivery of pre-existing drugs with improved targetability is the need of the hour. Enhanced delivery and targetability can ascertain improved bioavailability, reduced toxicity, decreased frequency of dosing and therefore better patient compliance. Nanoformulations are being explored for effective delivery of therapeutic agents, however, optimum specificity is not guaranteed. In order to achieve specificity, ligands specific to receptors or cellular components of macrophage and Mycobacteria can be conjugated to nanocarriers. This approach can improve localization of existing drug molecules at the intramacrophageal site where the parasites reside, improve targeting to the unique cell wall structure of Mycobacterium or improve adhesion to the epithelial surface of intestine or alveolar tissue (lectins). The present review focuses on the investigation of various ligands like Mannose, Mycolic acid, Lectin, Aptamers, etc., installed nanocarriers that are being envisaged for targeting antitubercular drugs.
Keywords: lectin